Testing for jumps in noisy high frequency data - AIT-SAHALIA, Yacine (Institutional Knowledge at Singapore Management University, 2012)
This paper proposes a robustification of the test statistic of Aït-Sahalia and Jacod (2009b) for the presence of market microstructure noise in high frequency data, based on the pre-averaging method of Jacod et al. (2010). We show that the robustified statistic restores the test's discriminating power between jumps and no jumps despite the presence of market microstructure noise in the data.